LIE AND HISTORY. THE CONCATENATION OF EVENTS BASED ON LYING BY SOME PERUVIAN HEAD OF STATE OF THE XXI CENTURY - DE LA CRUZ VILLANUEVA, Carlos (2023)
The following historical essay aims to describe a pattern of social behavior, shown from certain events, which concatenated reveal a complex social and characteristic manifestation of some of the leaders of Peru in the XXI century. The behavior that we will analyze, under the approximations of the history of the imaginary, will be the lie or some examples of arguments or uncertain proclamations that the leaders make. This exercise of historical observation will be of vital utility, for the understanding and identification of a temporal pattern of events, on which the use of lies is expressed, as a mechanism aimed at protecting the image of the ruler, as long as, the deception generated is not discovered. Well, when evidenced, a scandal is produced, which becomes a historical event, which will be the scene of the destruction of the image of the ruler, who cannot hide the truth of his political actions, will be criticized, and questioned by the population.